The Effect of Resveratrol on The Oxidative Stress in Rats Treated with Irradiation - Ozcelik, Mehtap; Erisir, Mine; Guler, Osman; Baykara, Murat; Bulmus, Funda Gulcu (Ataturk Universitesi, 2020)
The antioxidant and protective effect of resveratrol against irradiation induced oxidative damage were researched. Twenty-one rats were seperated into 3 groups; First group was the control group. Second group was the irradiation group; received physiological saline intraperitoneally (i.p.) for three days, then 9 Gray (Gy) irradiation was applied. Third group was irradiation+Resveratrol group; received 10 mg/kg resveratrol i.p. for three days and then the same dose of radiation was applied. As a result of irradiation, a significant increase was found in the level of malondialdehyde (MDA) in the liver, kidney and brain tissues of rats (P<0.001). Glutathione peroxidase (GSH-Px) activity in all the tissues and superoxide dismutase (SOD) activity, Glutathione (GSH) levels in liver decreased (P<0.01), GSH levels in kidney, spleen and ovarium tissues significantly increased (P<0.05). The giving of resveratrol significantly reduced the MDA levels increasing in liver, kidney, and brain as a result of irradiation (P<0.001) and the liver MDA levels reached to the control levels. By giving resveratrol, it was determined that all the antioxidants studied reduced significantly compared to the control group and/or the irradiation group (P<0.05). According to the data obtained as a result; It was concluded that resveratrol shows a corrective effect by changing the oxidant/antioxidant balance against oxidative stress caused by irradiation, therefore resveratrol is a powerful antioxidant. © 2020 Ataturk Universitesi. All rights reserved.
Keywords: Irradiation; Oxidative stress; Resveratrol